The Influence of Soil Moisture and Rotation Speed of Rotary Tiller On The Characteristics of Tilt Soil - Wirosoedarmo, Ruslan (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
The aim of this research was to find out the best soil tilt as affected by the moisture content of the soil and rotation speed of rotary tiller. A randomized block design experiment was conducted at Balai Benih Induk Palawija, Bedali Lawang, Malang Regency, from October 2002 until January 2003, in three replicates.Â The measurements were carried out on the tilt soil i.e. the tillage depth and mean weight diameter, the porosity and bulk density of soil, surface roughness of soil, penetration resistance of soil and shear strength of soil. The results indicated that both, the moisture content of soil as well as the rotation speed of the rotary tiller and their interactions significantly affects the above-mentioned parameters. The best tilt soil was found on the use of the rotary tiller at 90 rpm on the soil having moisture content plastic limit of 1.0 and the tillage was carried in two times. Â Key words: Rotary tiller, moisture content, rotary speed, plastic limit